DAMP and DIC: The role of extracellular DNA and DNA-binding proteins in the pathogenesis of DIC. Issue 4 (July 2016) - Liaw, Patricia C.; Ito, Takashi; Iba, Toshiaki; Thachil, Jecko; Zeerleder, Sacha
Abstract: Disseminated intravascular coagulation (DIC) is a heterogeneous group of disorders, which manifest as a spectrum of haemorrhage and thrombosis complicating many primary conditions including sepsis, trauma and malignancies. The pathophysiology of this condition is complex. In the recent years there is growing evidence that damage associated molecular patterns (DAMPs) play a crucial role in the pathogenesis of DIC. Upon cell-death and/or cell activation of hematopoietic and parenchymal cells extracellular cell-free DNA as well as DNA binding proteins (e.g. histones and high mobility group box 1 protein [HMGB1]) are released into circulation. This release is a highly regulated process mediated among others by serine proteases, such as factor VII-activating protease (FSAP) and DNase1. Circulating cell-free DNA has been demonstrated to influence primary and secondary hemostasis by inducing platelet aggregation, promoting coagulation activation, inhibition of fibrinolysis and directly interfering with clot stability. In this respect cell-free DNA in tissue as well as released into the circulation after neutrophil activation in the form of neutrophil extracellular traps (NETs) has been shown to be cytotoxic and highly procoagulant. DNA-binding proteins such as histones and HMGB1 are also strongly procoagulant and are involved in the pathogenesis of DIC. The present review gives an overview on how extracellular DNA is released into circulation and the structure of circulating DNA. In addition it summarizes the effect of extracellular DNA and DNA-binding proteins on platelet activation, plasmatic coagulation as well as fibrinolysis.